2019
DOI: 10.1177/1357633x19856156
|View full text |Cite
|
Sign up to set email alerts
|

Telecare management of pain and mood symptoms: Adherence, utility, and patient satisfaction

Abstract: Introduction Pain, depression, and anxiety are prominent symptoms that frequently co-occur, causing significant debilitation and frequent primary care visits. This paper examines the acceptability of telecare and self-management modules in managing these conditions in a randomized trial. Methods The Comprehensive Management of Mood and Physical Symptoms (CAMMPS) trial compared an automated symptom management (ASM) plus self-management intervention with a comprehensive symptom management (CSM) intervention that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
(34 reference statements)
1
9
0
Order By: Relevance
“…8 The satisfaction assessment for validating innovative health models is an important tool for monitoring their implementation strategies and special attention should be given when such strategies focus on populations in vulnerable situations. 20 Several tools are described to assess satisfaction [21][22][23][24][25][26] but their performance in vulnerable populations can be challenging due to the less adherence and possible difficulty in understanding complex questionnaires. According to Mair et al, few studies had a population larger than 100 patients, most of those studies identified that telehealth was an acceptable consultation model due to the increased access to specialized services and the lower need for travel and time involved to realize the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…8 The satisfaction assessment for validating innovative health models is an important tool for monitoring their implementation strategies and special attention should be given when such strategies focus on populations in vulnerable situations. 20 Several tools are described to assess satisfaction [21][22][23][24][25][26] but their performance in vulnerable populations can be challenging due to the less adherence and possible difficulty in understanding complex questionnaires. According to Mair et al, few studies had a population larger than 100 patients, most of those studies identified that telehealth was an acceptable consultation model due to the increased access to specialized services and the lower need for travel and time involved to realize the consultation.…”
Section: Discussionmentioning
confidence: 99%
“…There is possibly an unmet need relating to facilitation of person centred care that has not been well supported during lockdown. Whilst physical interventions may be restricted, learning from other disciplines and application to virtual foot health consultation could provide useful facilitation of supported selfmanagement [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has, on occasion, been framed as a ‘mechanization’ of medicine and medical practice in extant studies, which have cited patients’ desire for more human interaction (Bushey et al., 2020) and user friendliness (Hadwich et al., 2010). However, these insights are not mirrored in the shared experiences of physicians on Twitter.…”
Section: Research Findingsmentioning
confidence: 99%